Electrochemical properties of LiNi0.8Co0.1Mn0.1O2 synthesized by sol-gel and co-precipitation methods - Tung, Mai Thanh; Luong, Vu Duc (Vietnam Journal of Chemistry, 2016)
Layered LiNi0.8Co0.1Mn0.1O2 cathode materials have been prepared by sol-gel and co-precipitation methods. The structural, morphological and electrochemical properties of the materials were compared. The XRD patterns show that both the sol–gel and the co-precipitation method formed single phase materials with good layered characteristics. Electrochemical tests indicate that the material prepared by the co-precipitation method has slightly better electrochemical properties, with an initial discharge capacity of 185 mAhg−1 and capacity retention of 96.85 % after 50 cycles at a cycling rate of 1.0 C, as well as better capability at 7 C. The improved performances of the co-precipitation synthesized material may be attributed to the low Li/Ni disorder